The Christmas Toy Factory - Geronimo Stilton
Enter the world of Geronimo Stilton, where another funny adventure is always right around the corner. Each book is a fast-paced adventure with lively art and a unique format kids 7-10 will love. Ho, ho, ho! I love Christmas in New Mouse City. But this year, Grandfather William wanted me to research a new story. He asked me to dress up like Santa Claus and let lots of little mouselets sit on my lap. Cheese niblets! If only I had my own team of reindeer and could fly far, far away. . . .